2015
DOI: 10.1016/j.jfda.2014.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Safety assessment of menaquinone-7 for use in human nutrition

Abstract: Vitamin K occurs widely in foods and has been shown to have a beneficial effect on the cardiovascular system, as well as anticancer, anti-inflammatory, and antiosteoporosis properties. A previous study indicates that long-chain menaquinone-7 may be more bioavailable than vitamin K and short-chain menaquinones. In the present study, acute, subacute toxicity and genotoxicity assays were carried out to evaluate the safety of oral menaquinone-7 in albino Wistar rats. Oral administration of menaquinone-7, at a conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Nevertheless, a number of preclinical and clinical studies confirmed the safety of VK consumption. Several times higher dose levels than the estimated dietary intake for MK-7 did not show any toxicity in experimental animals [35]. In clinical studies, very high doses of MK-4 were used in the treatment of osteoporosis with no side effects [36].…”
Section: Introductionmentioning
confidence: 96%
“…Nevertheless, a number of preclinical and clinical studies confirmed the safety of VK consumption. Several times higher dose levels than the estimated dietary intake for MK-7 did not show any toxicity in experimental animals [35]. In clinical studies, very high doses of MK-4 were used in the treatment of osteoporosis with no side effects [36].…”
Section: Introductionmentioning
confidence: 96%
“…It was reported that MK-7 is a component of microbial plasma membranes and plays an important role in electron transport and oxidative phosphorylation [ 4 , 5 ]. Owing to its good bioavailability, MK-7 functions in protecting human health [ 6 ] by preventing osteoporosis [ 7 ], arterial calcification, cardiovascular disease, and Parkinson disease [ 8 , 9 ]. The cost of treating osteoporosis and cardiovascular diseases is high and will likely increase with the aging of populations.…”
Section: Introductionmentioning
confidence: 99%
“…The adverse effects of menaquinones, including Menaquinone-7 has been investigated in several animal and in vitro toxicity studies. Findings from animal studies for acute, chronic, and genotoxicity and in vitro studies for mutagenicity and carcinogenicity showed no significant risks associated with exposure to menaquinones [3]. The absence of adverse effects or death suggest that the minimum lethal dose of Menaquinone-7 is greater than 2000 mg/kg bw [4].…”
Section: Menaquinone-7 Safetymentioning
confidence: 95%